Investigating the Meaning and Masseges of the Mappacci Wedding Party in Buginess Tradition - Usman M; Muhammad Hanafi; Ika Rama Suhandra; Sam Hermansyah; Isumarni Isumarni; Anjali Anjali (La Ogi : English Language Journal, 2023)
This study examines the meaning and message of a tradition that has a very deep meaning. This thesis aims to find out the meanings and messages contained in the traditional Buginess mappacci culture in Sidenreng Rappang. This study uses qualitative research methods with analysis using the theory of Charles Sanders Pierce.From the results of the study, it was revealed that the preparation and procession in mappacci is a Bugis custom whose implementation uses leafs, mappacci is a form of hope and prayer, for the welfare and happiness of the prospective bride and groom, which is arranged in a word summary of nine types of equipment. Pillows, silk covers, jackfruit leaves, banana shoots, pacci leaves, rice, candles, pacci holders, brown sugar, and coconut. That is the meaning contained in the mappacci ceremonial equipment which is always carried out at every Bugis traditional wedding in Sidrap Regency. Pacci leaf is a kind of plant in Indonesian, henna plant, and in Latin, it is called lawsania alba which means to clean or purify oneself. Thus the implementation of mappacci contains a symbolic meaning of cleanliness or holiness which aims to cleanse the soul and body of the prospective bride and groom before navigating the household ark. The uniqueness of this tradition can be seen from the social stratification in the mappacci procession, namely the giving of silk sarongs where people who are not of noble descent give seven silk sarongs while those of noble descent give nine silk sarongs. The meaning and message are contained in the mappacci process because it contains a good meaning and purpose.Based on the conclusions of the research, the researchers suggest: The Bugis community maintains the culture that has been inherited from the culture of their ancestors and it is hoped that the younger generation can preserve that culture, where the Bugis mappacci traditional wedding culture contains values ​​and meanings for the message of life mean well.